Analysis of nail properties for joint design. (15th October 2018) - Sandhaas, Carmen; Görlacher, Rainer
Highlights: Database with more than 9000 individual test results of nails has been assembled. The yield moment can be calculated using tension test results. Withdrawal and head pull-through parameters must be experimentally determined. The introduction of technical classes in Eurocode 5 is recommended. Abstract: Design of nailed joints requires properties such as yield moment, tensile strength, withdrawal or head pull‐through parameters. These properties are either given as empirical equations in codes or, especially for profiled nails, in technical documents for the individual nails. This is not only cumbersome; it also requires considerable testing effort from nail producers. Based on an extensive database comprising more than 9000 test results carried out for certification purposes, analyses were carried out in order to develop more reliable input parameters for the design of nailed joints. It could be shown that the yield moment can be correctly calculated using nail tensile test results. The withdrawal and head pull‐through parameters need to be experimentally determined also in future. The introduction of technical classes to which the individual nails are assigned, containing different numerical values for the input parameters, would facilitate the work of practitioners considerably as the need to consult a large number of technical documentation would not be necessary anymore.